A inclusão do aluno surdo no ensino regular na perspectiva de professores do Ensino Fundamental - FERRÃO, Cleomárcio Pereira (2019)
This article aims to answer the following question: what are the prospects of two teachers of General Gurjão School in Belem on the process of school inclusion of deaf students? With this we aim to: Identify the prospects of these teachers of General Gurjão School in Belém on the process of school inclusion of deaf students. Even as: Understanding what the teacher expects of inclusive school and difficulties are faced by teachers in school life in inclusive class; Check ff the school is suitable to meet the expectations of the teacher and the deaf students; Identify the limits and possibilities pointed out by these teachers in their teaching together with these deaf students. This research is a qualitative basis, with a case study and a field survey of the two teachers through semi-structured interviews. It has been found through these interviews that teachers do not have a dedicated training to meet these deaf students with a comprehensive education quality, taking into account their deaf culture and the needs of each student in the inclusion process. We suggest that, for better implementation of inclusive education, the knowledge of all of the sign language used by deaf communities need. Thus arises the proposal of bilingual education that places the sign language of the deaf as their own, which is acquired first. And from this language that the deaf should contact the majority language of their social group, and for him his second language.